WorldFish Carp Genetic Improvement Program Pond Books 2023 - Hamilton, Matthew; Shanta, Sirajum Monira; Akhter, Md (2024)
WorldFish Carp Genetic Improvement Program Pond Books 2023 include data on pond inputs, environment, fish deaths and transfers.